2006
DOI: 10.1080/00365520600609941
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of perianal fistulas in Crohn's disease by local injection of antibody to TNF-α accounts for a favourable clinical response in selected cases: A pilot study

Abstract: Local injections of infliximab along the fistula tract seem to be an effective and safe treatment of perianal fistulas in Crohn's disease. However, further controlled clinical investigations are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…Two prospective studies25 26 assessed responses to EUA and local injection of anti‐TNFα drugs. In one study26, 11 patients received between three and five injections, and eight patients achieved remission (cessation of fistula drainage) at the end of the treatment course.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature about local injections of infliximab for extradermatological indications is increasing. It has essentially been used intralesionally in Crohn’s diseases [10,11,12] and in rheumatoid arthritis [13]. The first reports concern intra-articular infusion of the drug in inflammatory joint diseases and the last report to date is about intravitreal administration for neovascular age-related macular degeneration [14].…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled, observational pilot studies have been carried out using infliximab [106][107][108] and adalimumab [109,110], and the results are reported as promising. However, the characteristics of these studies do not justify the use of this method in everyday clinical practice.…”
Section: Perianal Fistulasmentioning
confidence: 99%